Settlement of Shallow Foundation in Dry Sand Under an Earthquake - Mohammed Al-Neami; Falah Rahil; Ahmed Hussain (Engineering and Technology Journal, 2021)
Seismically induced settlement of buildings with shallow foundations resting on dry sand soils has resulted in severe damage in recent earthquakes. A multi-degree of freedom shaking table and a fixed container were manufactured and used to study the foundation settlement. Series of shaking experiments on the shallow foundation situated in a center of the container and atop of a dry sandy soil has been performed to identify the mechanisms involved to calculate the foundation settlement induced by earthquake shaking. In this research, the important factors are identified, including shaking intensity, the soil relative density, the degree of freedom and the building’s weight. Two relative densities (55 % and 80%) are used and three local magnitudes of earthquakes (5.8, 6.4, and 7.2) (Anza, Jalisco, and Guerrero) respectively with one and two degrees of freedom. The results of the shaking indicated that shallow foundation settlement on the dry sand increases with the increase of the local magnitude of earthquakes and maximum acceleration. In the case of Anza, the percentage decrease in the settlement between the relative density of 55% and 80% for systems (x and xy) is (47% and 42%) respectively. While in the case of Jalisco and Guerrero, the percentage decreases in their settlement and for the same systems is (11% and 57%), (36% and 36%) respectively. The degree of freedom has an impact on the foundation settlement; it is proportional to the degree of freedom. Also, the results show that the settlement decreases when the relative density of sand increases.